Urban heat islands and electrical energy consumption - Souza, L. C L [UNESP]; Postigo, C. P. [UNESP]; Oliveira, A. P. [UNESP]; Nakata, C. M. [UNESP] (Taylor & Francis, 2009)
This study proposes the development of thermal and energy consumption maps to generate useful planning information. A residential neighbourhood in a medium-sized city was selected as the study area. In this area, 40 points were taken as urban reference points where air temperatures at the pedestrian level were collected. At the same time, rural temperatures made available by the city meteorological station were registered. Data of electrical energy consumption of the building units (houses and apartments) were collected through a household survey that was also designed to identify the users' income levels. Then, maps were developed so that the configuration of urban heat islands and electrical energy consumption could be visualised, compared and analysed. The results showed that the income level was the most important variable influencing electrical energy consumption. However, a strong relationship of the consumption with the thermal environment was also observed.
Keywords: Energy consumption; GIS; Thermal environment; Urban heat islands; Geographic information systems; Surveys; Air temperatures; Building units; Electrical energy consumption; Household surveys; Income levels; Meteorological stations; Neighbourhood; Planning informations; Reference points; Study areas; Energy conservation; conference proceeding; electricity; energy use; heat island; household survey; neighborhood; residential energy; visualization